α-Synuclein Aggregated with Tau and β-Amyloid in Human Platelets from Healthy Subjects: Correlation with Physical Exercise - Daniele, Simona; Pietrobono, Deborah; Fusi, Jonathan; Lo Gerfo, Annalisa; Cerri, Eugenio; Chico, Lucia; Iofrida, Caterina; Petrozzi, Lucia; Baldacci, Filippo; Giacomelli, Chiara; Galetta, Fabio; Siciliano, Gabriele; et al. (Frontiers in Aging Neuroscience, 2018)
The loss of protein homeostasis that has been associated with aging leads to altered levels and conformational instability of proteins, which tend to form toxic aggregates. In particular, brain aging presents characteristic patterns of misfolded oligomers, primarily constituted of β-amyloid (Aβ), tau, and α-synuclein (α-syn), which can accumulate in neuronal membranes or extracellular compartments. Such aging-related proteins can also reach peripheral compartments, thus suggesting the possibility to monitor their accumulation in more accessible fluids. In this respect, we have demonstrated that α-syn forms detectable hetero-aggregates with Aβ or tau in red blood cells (RBCs) of healthy subjects. In particular, α-syn levels and its heteromeric interactions are modulated by plasma antioxidant capability (AOC), which increases in turn with physical activity. In order to understand if a specific distribution of misfolded proteins can occur in other blood cells, a cohort of human subjects was enrolled to establish a correlation among AOC, the level of physical exercise and the concentrations of aging-related proteins in platelets. The healthy subjects were divided depending on their level of physical exercise (i.e., athletes and sedentary subjects) and their age (young and older subjects). Herein, aging-related proteins (i.e., α-syn, tau and Aβ) were confirmed to be present in human platelets. Among such proteins, platelet tau concentration was demonstrated to decrease in athletes, while α-syn and Aβ did not correlate with physical exercise. For the first time, α-syn was shown to directly interact with Aβ and tau in platelets, forming detectable hetero-complexes. Interestingly, α-syn interaction with tau was inversely related to plasma AOC and to the level of physical activity. These results suggested that α-syn heterocomplexes, particularly with tau, could represent novel indicators to monitor aging-related proteins in platelets.